Modulation as variation in target-language translation equivalence - Durjava, Iza (ELOPE (Ljubljana), 2012)
Modulation in translation theory is usually observed as a procedure involving a change in point of view in the target-language text. The paper introduces a newly modified concept of perceiving the process as variation in two or more Slovene translation equivalents corresponding to a single English collocation of the source text. The reasons or conditions for such modulation can be sought in collocations representing a loosely fixed word combination and thus often allowing variation on the syntagmatic axis, collocations as a minimum context and extended minimum context, co-text as a whole, and TL situation.
Keywords: angleščina; English; kolokacija; modulacija; prevajanje; Slovene; slovenščina; sobesedilo; translation